2023
DOI: 10.1063/5.0139960
|View full text |Cite
|
Sign up to set email alerts
|

Drop impact phenomena and spray cooling on hot nanotextured surfaces of various architectures and dynamic wettability

Abstract: Spray cooling has been used to quench metal slabs during casting, cool nuclear reactors, suppress accidental fires, and remove heat from high-power density electronics. In particular, the miniaturization of electronic devices inevitably results in an increased power density or heat flux on the microelectronics surfaces and poses a threat of a thermal shutdown of such devices when cooling is insufficient. Surface nanotexturing effectively augments additional liquid-to-substrate surface area, thereby increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…), 1 Young-Su Ko (고영수), 1 Byeong Eun Jeon (전병은), 1 Prosenjit Sen ( ), 2 and Choongyeop Lee (이충엽) 1,a) I. INTRODUCTION Over the years, researchers have extensively investigated the dynamics of drop impact on solid surfaces due to its diverse applications in biomedical diagnostics, 1 food processing 2 and chemical industries, 3 electronic industries, 4 and rapid prototyping. 5,6 Notably, it has been demonstrated that drop impact on a mesh with micropores can serve as a mechanism to generate microdroplets.…”
Section: Dynamics Of Microdroplet Generation Via Drop Impact On a Sup...mentioning
confidence: 99%
“…), 1 Young-Su Ko (고영수), 1 Byeong Eun Jeon (전병은), 1 Prosenjit Sen ( ), 2 and Choongyeop Lee (이충엽) 1,a) I. INTRODUCTION Over the years, researchers have extensively investigated the dynamics of drop impact on solid surfaces due to its diverse applications in biomedical diagnostics, 1 food processing 2 and chemical industries, 3 electronic industries, 4 and rapid prototyping. 5,6 Notably, it has been demonstrated that drop impact on a mesh with micropores can serve as a mechanism to generate microdroplets.…”
Section: Dynamics Of Microdroplet Generation Via Drop Impact On a Sup...mentioning
confidence: 99%
“…1 Many of those brous materials are produced from polymer solutions, [2][3][4] which may contain additives such as nanoparticles, nanotubes, or soluble precursors. 3,[5][6][7][8][9][10] The polymer matrix either serves as a template for micro/nanober fabrication or is the material of interest itself. The applications of such polymer bers are determined not only by the structure of the polymer's repeating building block or their physicochemical surface properties but also by their dimensions, such as their length and diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Rybicki and Mudawar [10] concluded that the volumetric flux and droplet diameter are the most significant spray parameters influencing the heat transfer at spray cooling. Plenty of work has also been carried out on the heat transfer aspect of a single drop [11][12][13] or drop train flows [14][15][16][17]. Although they revealed that the droplet impact has a significant effect on the cooling performance, for a clear understanding of heat transfer associated with irrigation patterns during spray cooling, further research is still needed [18].…”
Section: Introductionmentioning
confidence: 99%